Einige Blattlaus-Schlupfwespen aus Israel (Hymenoptera: Braconidae, Aphidiinae). - Mackauer, Manfred (Contributions to Entomology = Beiträge zur Entomologie, 1959)
The present paper deals with occurrence, distribution and host specifity of different species of the genera Ephedrus Haliday 1833, Praon Haliday 1833 and Trioxys Haliday 1833 (Hymenoptera: Braconidae, Aphidiinae) found in Israel up to now. The new species Ephedrus palaestinensis n. sp. is described, some further host aphids have been recorded.Nomenclatural Actspalaestinensis Mackauer, 1959 (Ephedrus (Ephedrus)), spec. n.